Retorika âKebenaran Tungalâ: Peran Kyai terhadap Laku Hidup Perempuan Sunda di Pesantren - R, Navita Hani (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
This paper talked about the role of Kyai and its power relations in influencing the lives of women in traditional âpesantrenâ in Sundanese society through the lens of structural functionalism theory. Sundanese society were the people who uphold the principles of Islam, it was not surprising that âpesantren âand Kyai quite well developed in that area. The role and position of Kyai considered very major in Sundanese society. Kyai in the Sundanese society not only as a teacher or a person who was an expert in religion, he also acted as society solidarity guard. The Strategic Role of the Kyai in maintaining social stability and collective solidarity also had influence on the behavior of women living in âpesantrensâ Sundanese - West Java. Women built and reworded by Kyai said. He should be at home, caring for and maintaining the child, as well as comply with the husband. Earlier in the Sundanese cultural context, women had a power over domestic space, but in a pesantren, where the teaching of Islam is very strong applied, women no longer had good power in the domestic sphere especially in public areas. The duties of women entirely set in ujaran- speech Kyai they must obey. Womens lived in the pesantren very different from ordinary women. Although Islam in Sundanese had finely mixed with local traditions, but still more women at the school based on the teachings of Islam. Each of what was presented by Kyai was the truth that comes from God.